2001
DOI: 10.1002/14651858.cd000561
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants versus placebo for the depressed elderly

Abstract: Background Depression warranting intervention is found in ten percent of people over the age of 60. Older depressed people are more likely to die than non-depressed. Relatively few receive therapeutic interventions, and those that do, tend to receive low dose antidepressant therapy. Depression in older people is thought to di er in terms of aetiology, presentation, treatment and outcome than in younger people. Concomitant physical illness and increasing social, physical and neurophysiological diversity are ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
103
0
7

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(119 citation statements)
references
References 79 publications
8
103
0
7
Order By: Relevance
“…These studies support the clinical observation that antidepressants can effectively treat depression in the elderly, the same conclusion reached by others using meta-analytic techniques (Mittmann et al, 1997;Wilson et al, 2001). Our NNT analysis demonstrated that one must treat eight patients to have one subject achieve even a 50% reduction in depressive symptoms; thus, while antidepressants are more effective than placebo, a significant number of patients will not respond.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These studies support the clinical observation that antidepressants can effectively treat depression in the elderly, the same conclusion reached by others using meta-analytic techniques (Mittmann et al, 1997;Wilson et al, 2001). Our NNT analysis demonstrated that one must treat eight patients to have one subject achieve even a 50% reduction in depressive symptoms; thus, while antidepressants are more effective than placebo, a significant number of patients will not respond.…”
Section: Discussionsupporting
confidence: 89%
“…We performed a systematic review of all published randomized, placebo-controlled antidepressant medication trials in populations over age 55 years. Papers were obtained via MEDLINE (1966( -August 2003 and PSYCINFO (1872-August 2003. Unpublished trials, trials examining nonpharmacologic interventions, and papers reporting post hoc analyses were not included in this review unless they provided new insights.…”
mentioning
confidence: 99%
“…Depression is a treatable illness [19] ; approximately 50-60% patients with major depressive disorder are thought to improve clinically as a consequence of antidepressant treatment [20,21] . In addition, there are other indications to prescribe an antidepressant.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological intervention is often a first-line approach to treat clinically diagnosed anxiety (Flint, 2005) and depression (Wilson, Mottram, Sivananthan, & Nightingale, 2001) in older people.…”
Section: Interventions For Loneliness Anxiety and Depression In Oldementioning
confidence: 99%
“…The pharmacological interventions for depression involve antidepressants. Selective serotonin reuptake inhibitors and monoamine oxidase inhibitors were all found effective in comparison to placebos when treating depression among institutionalised older people (Wilson et al, 2001). Anxiolytic medications such as benzodiazepines are the most common pharmacological treatment for anxiety in older people (Lindsey, 2009).…”
Section: Treatments For Loneliness Anxiety and Depression In Older Pmentioning
confidence: 99%